Targeting Mutational Landscape of TP53 in patients diagnosed with Oral Cancer living in Senegal - Pierre Diaga, SARR; Silly, TOURE; FAHIME Elmostafa, EL; Jean Pascal Demba, DIOP; Seydi Abdoul, BA; Yacouba, DIA; Babacar, MBENGUE; Maguette, SYLLA-NIANG; Alioune, DIEYE; Rokhaya, NDIAYE-DIALLO (Journal of Cancer Genetics And Biomarkers, 2022)
Introduction Genomic mutations in TP53 gene in association with etiological risk factors have been associated with oral carcinogenesis. Herein, we screened for genomic variants of TP53 predisposing to oral cancers in Senegalese patients. Methodology 88 patients with confirmed diagnostic were recruited after informed consent. Blood samples were collected from each patient to perform DNA extraction, PCR amplification of all coding exons of TP53 followed by Sanger Sequencing of PCR products. Nucleotide sequences were analysed with Genalys software. 94 blood donors with no cancer diagnosis were also recruited as controls for association study between the most common variants identified in patients and predisposition to oral cancers. Results Sequence analysis showed that 52.27% of patients carry at least one mutation in TP53. Eleven genomic variants were identified, 7 variants already reported in databases and 4 new variants. The most recurrent variants in this study already reported as cancer-related variants were Pro72Arg (rs1042522; Arginine frequency estimated at 31.26%) and a 16 bp insertion in intron 3 (rs59758982; allelic frequency estimated at 26.25%). Haplotype analysis between these variants showed a strong linkage disequilibrium (D’ = 0.999, r2 = 0.153 and p-value < 0.05). However, association study did not find any significant association with susceptibility to oral cancer (p-value > 0.05). Conclusion Our study highlighted that despite the absence of association between the two most common cancer-related variants in Senegalese patients diagnosed with oral cancer, their strong LD suggested that they could be transmitted together in a common haplotype which may be implicated in oral carcinogenesis.
Keywords: TP53 gene; Genomic variant; Senegal; Oral cancers; susceptibility